Convincing and Cheating Act In â€œCatch Me If You Canâ€ Movie Script by Steven Spielberg - Helen Jaya Rigai; La Aso; Ela Martisa (ELITE: Journal of English Language and Literature, 2020)
This study aims at revealing the perlocutionary act that is used in the movie â€œCatch Me if You Canâ€. The movie contains many perlocutionary acts which are cheating and convincing acts. Both acts are done by the main character and other minor characters who have conversations with the main character. The perlocutionary act which is analyzed in this study is limited to only convincing and cheating acts because both acts are done many times by the main character and other characters. The writer applies the qualitative descriptive method to analyze the study. The data collection technique of this study includes downloading, watching, classifying, and coding the data. To analyze the collected data the writer applies several techniques such as identifying the data, describing the data, categorizing the data, analyzing, and concluding the data. The result of this study is there are 7 data (38%) of the convincing acts and 13 data (72%) of the cheating acts. The cheating act is the most dominant act found in the movie and mostly is done by Frank as the main character. Frank goes around the aviation company as a co-pilot to be able to cash the fraudulent checks. The bank and the aviation company end up believing in Frank and cash the checks for him. Frank does the cheating act of perlocutionary act to make other people do what he wants them to do.